2020
DOI: 10.5194/acp-20-11399-2020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of global ship emissions on European air pollution levels

Abstract: Abstract. Ship emissions constitute a large, and so far poorly regulated, source of air pollution. Emissions are mainly clustered along major ship routes both in open seas and close to densely populated shorelines. Major air pollutants emitted include sulfur dioxide, NOx, and primary particles. Sulfur and NOx are both major contributors to the formation of secondary fine particles (PM2.5) and to acidification and eutrophication. In addition, NOx is a major precursor for ground-level ozone. In this paper, we qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…(1) With the increase of exposure time of the glass sheet to the air, the deposition process of air pollutants on the surface of the long-standing glass slide approaches a transition process from discontinuous deposition to uniform coverage, which also directly leads to the overall trend of RMS roughness value first rising and then falling over time (2) The surface of the glass slide after being placed for a long time only has the accumulation of pollutants on the physical level, and there is no new generation of compounds on the chemical level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) With the increase of exposure time of the glass sheet to the air, the deposition process of air pollutants on the surface of the long-standing glass slide approaches a transition process from discontinuous deposition to uniform coverage, which also directly leads to the overall trend of RMS roughness value first rising and then falling over time (2) The surface of the glass slide after being placed for a long time only has the accumulation of pollutants on the physical level, and there is no new generation of compounds on the chemical level.…”
Section: Discussionmentioning
confidence: 99%
“…Outdoor air pollution, often called air pollution, is primarily caused by industrial waste gas and traffic exhaust. Studies have shown that air pollutants, such as sulfur dioxide, nitrogen oxides, and major particles, are the major contributors to the formation of PM2.5 [1,2]. South Korean researchers surveyed 249 administrative units on the relationship between long-term exposure to air pollutants and cardiopulmonary mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Among the variety of air pollution sources, ships emit particular large amounts of sulfur, carbonaceous aerosols and metals with substantial impacts on climate and public health (Corbett et al, 2007;Eyring et al, 2010;Viana et al, 2014;Jonson et al, 2020). Between 60,000 and 400,000 annual deaths by cardiopulmonary diseases and lung cancer as well as 14 million cases of childhood asthma were attributed to ship emissions (Sofiev et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The latest revision includes more stringent emission limits for NO x and SO 2 . In spite of these abatement regulations, the ship emissions of IMO registered vehicles and non-IMO registered vehicles show constant or slightly increasing trends for the compounds NO x , SO 2 , and PM 2.5 , as well as a clearly increasing trend for CO. Once the stringent regulation for fuel sulfur content (FSC) in marine fuel came into power in 2014, the emissions of SO 2 and PM 2.5 decreased rapidly at regional and global level (Johansson and Jalkanen, 2016;Johnsson et al 2020;Seppälä et al 2020).…”
Section: Introductionmentioning
confidence: 99%